Intervención del terapista respiratorio en paciente masculino de 68 años con enfermedad pulmonar obstructiva crónica. - Hinojoza Arboleda, Johely Pamela (2022)
Chronic obstructive pulmonary disease is a pathology with a high rate of prevalence and mortality on a global scale, which is characterized by intrapulmonary and extrapulmonary involvement. A clinical case of a 68-year-old male patient diagnosed with COPD is presented, who was admitted due to a clinical picture characterized by weakness, short-effort dyspnea and diaphoresis of hours of evolution plus tachypnea, tachycardia, intercostal retraction and desaturation of up to 86 %. The objective of this project was to define the intervention of the respiratory therapist in a 68-year-old male patient with chronic obstructive pulmonary disease. Having as a conclusion that the oxygenation, ventilation and respiratory rehabilitation physiotherapeutic measures constitute the cornerstone for the treatment of the different stages of this pathology.